(untitled) (Journal of the College of Languages (JCL), 2020)
The importance of research and study of classical Persian literature is not overlooked. So far, there have been many studies in this area. But there are still some things that need more research. Persian grammar is one of the most important branches of Persian literature. This section has always been converted at different times. One of the issues that has been neglected in the studies of classical literature is the study of the technical tales of past and past poetry. These texts can be studied from different perspectives. Because Persian is a mixed language, it is possible to combine language terms with each other or to add prefixes and suffixes to express new concepts. They can be used by examining nonlinear terms (derivative, compound, derivative) in the past, And used it to form new words. Saadi Shirazi has created valuable works in the field of Persian language and literature. Many scholars have tried to examine his works from different points of view. At the same time, sheikhs and cuttings were taken lightly. In this paper, the author attempted to study the composition of sati and parts. اهمیت تحقیق و پژوهش و واکاوی متون کلاسیک ادبیات فارسی بر کسی پوشیده نیست. تا کنون پژوهش های زیادی در این زمینه صورت گرفته است. ولی هنوز مواردی را نمى توان یافت که بررسی بیشتر درباره ی آنها ضروری به نظر می رسد. دستور زبان فارسی یکی از شاخه های مهم زبان فارسی است. این شاخه در ادوار مختلف همواره دستخوش تحول و دگرگونی بوده است. یکی از مواردی که در پژوهش های مربوط به ادب کلاسیک کمتر مورد توجه قرار گرفته است بررسی مباحث دستوری متون منظوم و منثور گذشته می باشد. این متون را می توان از نظرگاه های مختلف دستوری مورد مطالعه و مداقّه قرار داد. از آن جا که زبان فارسی زبانی ترکیبی است ؛ یعنی می توان از پیوستن واژه های زبان به یکدیگر یا افزودن پیشوندها و پسوندها به آن برای بیان مفاهیم تازه بهره گرفت ، می توان با بررسی واژه های غیر بسیط ( مشتق ، مرکب و مشتق ـ مرکب ) در آثار گذشتگان ، الگوی ساختواژه را از آنها استخراج کرد و در ساختن واژه های جدید از آن ها بهره برد. سعدی شیرازی آثار ارزشمندی را در حوزه ی زبان و ادبیات فارسی خلق کرده است .پژوهشگران بسیاری کوشیده اند تا آثار او را از دیدگاه های مختلف بررسی کنند. نگارنده در این مقاله کوشیده است تا به بررسی ترکیب‌سازی در قصاید و قطعات سعدی بپردازد.